2017
DOI: 10.1158/0008-5472.can-16-3480
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cystathionine-β-Synthase in Colonic Epithelia Reprograms Metabolism and Promotes Carcinogenesis

Abstract: The transsulfuration enzyme cystathionine-β-synthase (CBS) and its product hydrogen sulfide (H2S) are aberrantly upregulated in colorectal cancers, where they contribute to tumor growth and progression by both autocrine and paracrine mechanisms. However, it is unknown whether the CBS/H2S axis plays a role in colorectal carcinogenesis. Here, we report upregulation of CBS in human biopsies of precancerous adenomatous polyps and show that forced upregulation of CBS in an adenoma-like colonic epithelial cell line … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 41 publications
5
99
0
Order By: Relevance
“…Compared with normal bone samples, a total of 346 DEGs were identified in the osteosarcoma cells, containing 43 up-regulated and 303 down-regulated genes. CBS (cystathionine-β-synthase cancer), the most regulated gene in this study, was found to be upregulated in many types of tumors, such as multiple myeloma [ 14 ], colorectal cancers [ 15 ], bladder cancer [ 16 ] and et al, and downregulation of CBS help inhibit carcinogenesis. However, to our knowledge, there was no report about CBS in osteosarcoma, so it might be a novel target for the diagnosis or treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 80%
“…Compared with normal bone samples, a total of 346 DEGs were identified in the osteosarcoma cells, containing 43 up-regulated and 303 down-regulated genes. CBS (cystathionine-β-synthase cancer), the most regulated gene in this study, was found to be upregulated in many types of tumors, such as multiple myeloma [ 14 ], colorectal cancers [ 15 ], bladder cancer [ 16 ] and et al, and downregulation of CBS help inhibit carcinogenesis. However, to our knowledge, there was no report about CBS in osteosarcoma, so it might be a novel target for the diagnosis or treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 80%
“…In particular in human colon cancer, the most significant upregulation in tumor tissue (compared to surrounding tissue) was noted in CBS, with a trend for increase for 3-MST [26]. Likewise, in many human colon cancer cell lines, CBS was found to be highly expressed, and genetic silencing or pharmacological inhibition of CBS exerted antitumor effects in vitro and in vivo [24][25][26][37][38][39][40][41] while forced expression of CBS into non-transformed human epithelial cells increased their growth in situ (but did not render them metastatic) [42]. In contrast, in the current, murine colon cancer cell line, CBS (mRNA or protein) was undetectable (and, accordingly, the CBS inhibitor AOAA was without significant biological effects), while 3-MST was highly expressed.…”
Section: Discussionmentioning
confidence: 96%
“…The Boyden chamber cell migration assay was used as previously described (Phillips et al, 2017;Szabo et al, 2013). Briefly, 10 5 EA.…”
Section: Boyden Chamber Cell Migration Assaymentioning
confidence: 99%